2023
DOI: 10.1186/s13102-023-00645-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different rehabilitation training modalities on isokinetic muscle function and male athletes’ psychological status after anterior cruciate ligament reconstructions

Abstract: Background Previously, researchers reported performance enhancements following long-term plyometric training in athletes with anterior cruciate ligament reconstruction (LCA). However, the effects of combined eccentric and plyometric training on measures of isokinetic strength and psychological statues in male athletes have not been examined yet. Knowledge on the effects of combined eccentric and plyometric training help to better plan and program rehabilitations sessions and thus return-to-spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Figure 1 corresponds to item one when asked about which sport you practice frequently, achieving that the sport of soccer has a wide advantage over the other sports, thus the preferences to more than one sport are Fu=football 30% (362), At=athletics 9. 5 % (115), Ci=cycling 5.7% (69), Vo=volleyball 18.2% (220), Bc=basketball 7.4% (89), Bm=handball 4.0% (48), Am=martial arts 3.5% (42) and Ot=other sports 21.8% (263). It is clearly shown that the most preferred sport is soccer followed by volleyball.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 corresponds to item one when asked about which sport you practice frequently, achieving that the sport of soccer has a wide advantage over the other sports, thus the preferences to more than one sport are Fu=football 30% (362), At=athletics 9. 5 % (115), Ci=cycling 5.7% (69), Vo=volleyball 18.2% (220), Bc=basketball 7.4% (89), Bm=handball 4.0% (48), Am=martial arts 3.5% (42) and Ot=other sports 21.8% (263). It is clearly shown that the most preferred sport is soccer followed by volleyball.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is important to note that the duration of the plyometric training program can influence the results [41]. These can be particularly beneficial for elite athletes recovering from some surgery for sports injuries by combining different training approaches [42]. These findings provide valuable information for coaches and athletes seeking to improve their performance in all types of sports [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation